Universalization and Virtualization of the Market Economy, Financial and Real Economy and the Concept of Global Sustainable Development - Marković, Danilo Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Progress of knowledge has never occurred as quickly as in the twentieth century which has also led to changes in human civilization itself, the transformation of civilization in its informatization and virtualization. These two processes, closely connected and mutually dependent, have given human society special features so that the society, on the basis of these very features, has begun to identify with a special phase in its development just as it has begun to denote itself as an information and virtual society. The Author points to the developing nature of this type of society and thus to the realization of its basic traits. It as a society whose social-economic matrix is made up of neoliberal capitalism while its theoretical-cognitive matrix is made up of the postmodern. That is why it comprises in itself an affinity for efficiency and maximization of profit which is decisive for all the forms of social organization it embraces, while Truth, Goodness, Beauty and Justice do not function in it as understandable per se.
Keywords: neoliberal capitalism; virtualization; development; progress